2017
DOI: 10.1007/s11605-017-3446-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased Infiltration of Natural Killer and T Cells in Colorectal Liver Metastases Improves Patient Overall Survival

Abstract: High frequencies of NK and T cells in response to chemotherapy predict OS in CLM patients. These findings provide important insights that can help physicians to choose the best treatment option and adopt more predictive follow-up strategies for patients with CLM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 36 publications
2
63
0
4
Order By: Relevance
“…Consistently, it is in fact well known that human liver is highly enriched of cytotoxic antitumor lymphocytes including T and NK cells that exert immune-surveillance against cancer (72,84,85). Recently, also our group has showed how the presence of intratumoral infiltration of NK cells was an independent prognostic factor favoring overall survival after resection of CLM (86). Those data and results support how the host immune system represents an emerging hallmark of cancer (87) which should not be any more left to exploratory translational researches while it should be routinely considered in daily clinical practice.…”
Section: The Role Of the Host Immune Systemsupporting
confidence: 54%
“…Consistently, it is in fact well known that human liver is highly enriched of cytotoxic antitumor lymphocytes including T and NK cells that exert immune-surveillance against cancer (72,84,85). Recently, also our group has showed how the presence of intratumoral infiltration of NK cells was an independent prognostic factor favoring overall survival after resection of CLM (86). Those data and results support how the host immune system represents an emerging hallmark of cancer (87) which should not be any more left to exploratory translational researches while it should be routinely considered in daily clinical practice.…”
Section: The Role Of the Host Immune Systemsupporting
confidence: 54%
“…Several investigators have reported that patients with a relatively dense infiltration of malignant tumors by NK cells showed better clinical outcomes 18, 35, 36. Outcomes of NK cell‐target cell interactions are regulated by a fine integrative balance between inhibitory and activating receptors expressed on NK cells and their ligands on target cells 37.…”
Section: Discussionmentioning
confidence: 99%
“…The activation signal resulting from the engagement of NKG2D‐DAP10 overrides the inhibitory signal from MHC class I molecules leading to target cell lysis 30, 42. Reportedly, high density of intratumoral NKp46‐expressing NK cells was associated with OS in CRLM patients who received neoadjuvant chemotherapy 18. In this study, the expression of activation markers/effector molecules on both peripheral and liver NK cells of patients treated with neoadjuvant chemotherapy was enhanced compared with that in patients who did not receive chemotherapy; however, the proportion of NK cells among LMNC was reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other innate immune cells such as NK cells function in immune surveillance, vigilant for metastatic cells. There is a general consensus that NK cell cytotoxicity exerts a pivotal role against metastatic dissemination; indeed, an inverse correlation between metastasis and cytotoxic NK cell activity has been observed in renal , prostate , pancreatic , gastric , melanoma , breast , colorectal and lung cancer patients . Notably, the in vivo NK cell depletion by specific antibodies against NK cell receptors, results in increased metastatic burden in immunocompetent mice .…”
Section: Immune Surveillance During Metastasismentioning
confidence: 99%